Case Report: Dental Findings Can Aid in Early Diagnosis of APECED Syndrome - Brenchley, Laurie; Ferré, Elise M. N.; Schmitt, Monica M.; Gardner, Pamela J.; Lionakis, Michail S.; Moutsopoulos, Niki M. (Frontiers in Dental Medicine, 2021)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), also known as autoimmune polyglandular syndrome type 1 (APS-1), is a rare genetic disorder caused most often by biallelic mutations in the AIRE gene. Classic clinical findings of the disease are chronic mucocutaneous candidiasis and autoimmunity that primarily targets endocrine tissues, such as hypoparathyroidism and adrenal insufficiency. Recently, however, it has been appreciated that enamel hypoplasia, together with intestinal malabsorption and a characteristic APECED rash, is a prominent early disease manifestation of APECED which can aid in the diagnosis of disease before other potentially life-threatening disease manifestations occur. To demonstrate this point, we present data from a cohort of APECED patients, 70% of who present with enamel dysplasia at an early age. Importantly, early life presentation with enamel dysplasia was predictive of likelihood for subsequent APECED diagnosis. Furthermore, we present a case of a patient with APECED and severe enamel defects and discuss the utility of medical-dental professional co-operation in the diagnosis and management of this complex disorder.